The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1542/peds.2014-3544
|View full text |Cite
|
Sign up to set email alerts
|

Febrile Illness in an Infant With an Intracardiac Inflammatory Myofibroblastic Tumor

Abstract: We report a case of a child with a right ventricular inflammatory myofibroblastic tumor (IMT) who presented with fever, viral symptoms, and abdominal discomfort. Including this case, 49 intracardiac tumors have been previously reported in all age groups. The majority of intracardiac IMTs occur in pediatric patients, with approximately half presenting in children aged <12 months. Intracardiac IMTs are generally described as benign tumors; however, depending on their location, the initial presentation may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…56 In addition to myocardial infarction and tumour site derived symptoms, one-third of patients present with constitutional symptoms, such as fever, weight loss, malaise, and unspecific viral respiratory or gastrointestinal viral symptoms. 55,57 Echocardiographically, inflammatory myofibroblastic tumours appear as a heterogeneous mass arising from the endocardium. At cardiac magnetic resonance, the mass appears as isointense on T1, hypointense on T2 weight images and demonstrates intense delayed contrast enhancement.…”
Section: Inflammatory Myofibroblastic Tumoursmentioning
confidence: 99%
“…56 In addition to myocardial infarction and tumour site derived symptoms, one-third of patients present with constitutional symptoms, such as fever, weight loss, malaise, and unspecific viral respiratory or gastrointestinal viral symptoms. 55,57 Echocardiographically, inflammatory myofibroblastic tumours appear as a heterogeneous mass arising from the endocardium. At cardiac magnetic resonance, the mass appears as isointense on T1, hypointense on T2 weight images and demonstrates intense delayed contrast enhancement.…”
Section: Inflammatory Myofibroblastic Tumoursmentioning
confidence: 99%
“…Therefore, the variety of signs and symptoms can be presented by this tumour. Pang et al 11 reported a case of the right ventricular IMT in an 11-month-old infant presented with febrile illness. Oh et al 20 described an IMT in the appendix of an 85-year-old man with the history of gastric cancer.…”
Section: Outcome and Follow-upmentioning
confidence: 99%
“…Scientists believe that cytogenetic abnormalities play an important role. Apart from its biological characteristics, the discovery that IMT may harbor chromosomal rearrangements at the 2p23 Locus, where the gene site for anaplastic lymphoma kinase (ALK) is, also firmed the borderline neoplasm property of IMT[ 6 - 8 ]. According to several case reports, approximately 30 kinds of genetic rearrangement have been found in IMT, most of which are ALK fusion genes[ 9 - 12 ].…”
Section: Introductionmentioning
confidence: 99%